DILUTE PHASE VERTICAL PNEUMATIC CONVEYING OF CORK STOPPERS - Barbosa, R.; Pinho, C. (Revista de Engenharia Térmica, 2006)
The pneumatic conveying of cork stoppers is used in the cork processing industries with equipments designed and built purely on an empirical basis. Experimental studies to characterize this type of pneumatic transportation have been, so far, oriented towards the study of horizontal conveying processes, either for steady state transportation or for the acceleration zone. However studies were carried out on the determination of the pressure drop on vertical transportation of cork stoppers. Here the experimental apparatus and procedure are described, and the first experimental data that have been obtained are shown. In consequence a simple correlation for the pressure drop in the steady state region of the conveying pipe is proposed. The correlation is a function of dimensionless parameters used to characterize the two phase flow under analysis. Three standard stoppers sizes and a single pipe diameter were used in the experiments, all carried out at ambient temperature.